Egressos do mestrado e doutorado dos programas de pós-graduação em saúde coletiva: formação de origem e atuação profissional - Pereira, Maria Virginia Nunes [UNIFESP] (2014)
The purpose of this work is to rescue the origin and destination profile of the graduates on Public Health Post Graduation from the period from 1998 to 2007. The foundation of which is an ample assessment carried out by ABRASCO, investigating census data and forms completed online by the graduate. As well as the graduate?s age and gender, data such as the region of origin, background, labour market prospects, roles, functions, the institute in question and link. Updating the supremacy of female presence the results pointed to the quota growth in the period, particularly for doctorate. Alongside the growth of younger freshman excelled the coexistence with the presence of graduates over the age of 40 years. The data showed distinct regional settings - bigger female presence in the Northeast and Midwest and younger graduates in the South. Given the growing presence of graduates in the areas of Health Sciences it was observed the proportional decrease of doctors. The levels of nurses and nutritionists were sustained throughout the period and stood out, proportionally, the presence of other health professionals. In the case of Humanities, the presence of psychologists increased significantly, reaching 60 % of the category, to the detriment of the graduates in Social Work and Social Sciences. Meanwhile, when considering degrees from other areas, it pointed to a professional diversity of the clientele of Public Health Programs. Observing the regional variations of this composition, the study identified greater range of concentration of these professionals in the Southeast. Regarding the integration of graduates into the labour market, mostly prevailed references of exercising duties and functions in teaching, progressively followed by the increase of health professionals, administrators / managers, and finally, technicians and researchers. What prevailed among them was the trend as public servants, secondarily being referenced, and the link in CLT regime, more present within the education and administration / management. Beside different programmatic vocations the clientele can configure it is suggested the insertion of graduates into the labour market and endorses the fulfilment of the functions of Post Graduate Studies on education, research and care, articulated in the historic context defined by the policies of health and education.